Protocol to monitor activation of a two-component system in Dickeya dadantii during chicory leaf infection using Phos-tag gel - Edwige Madec; Jean-Marie Lacroix; Sébastien Bontemps-Gallo (STAR Protocols)
Summary: Quantifying the phosphorylation levels of proteins involved in bacterial signaling pathways is essential for understanding their role in stress adaptation and infection processes. Here, we present a protocol for the semi-quantitative assessment of the phosphorylation level of the transcriptional regulator CpxR during the infection process using Phos-tag gel. We describe steps for Dickeya dadantii infection of chicory leaves, followed by bacterial extraction, rapid acidic cell lysis, and subsequent protein analysis using Phos-tag SDS-PAGE and western blot.For complete details on the use and execution of this protocol, please refer to Bontemps-Gallo et al.1 and Cochard et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.